Renaturing Cities: Green and Blue Urban Spaces as Paradigms of Urban Planning. - Dall’O’, Giuliano (Springer, 2020)
Green in cities does not only play an aesthetic role but also contributes greatly to making the urban environment more sustainable in all senses of the term: environmental, energy-wise, economic and social. The purpose of this chapter is to tackle the issue of green in cities by highlighting the connections that exist between having a nature base or renaturing of cities and sustainable planning, stimulating the necessary in-depth analysis of a topic that must constitute an information resource for those who deal with green planning. The chapter, after an introduction that highlights the need to seek a new alliance between urban spaces and natural spaces, deals with the issue of urban infrastructure, highlighting its potential. The final part of the chapter deals with the issue of urban heat islands providing some improvement strategies.
Keywords: Grünplanung; Urbaner Raum; Nachhaltige Stadtentwicklung; Stadtbegrünung; Renaturierung; Naturraum; Stadtraum; Hitzebelastung; Gegenmaßnahme; Grüne Infrastruktur; Blaue Infrastruktur; Hitzeinsel